Bag‐1 promotes cell survival through c‐Myc‐mediated ODC upregulation that is not preferred under apoptotic stimuli in MCF‐7 cells. (15th July 2015) - Ozfiliz, Pelin; Kizilboga, Tugba; Demir, Salih; Alkurt, Gizem; Palavan‐Unsal, Narçin; Arisan, Elif Damla; Dinler‐Doganay, Gizem
<x xml:space="preserve">Abstract</x> Bag‐1, Bcl‐2 associated athanogene‐1, is a multifunctional protein that can regulate a wide variety of cellular processes: proliferation, cell survival, transcription, apoptosis and motility. Bag‐1 interacts with various targets in the modulation of these pathways; yet molecular details of Bag‐1's involvement in each cellular event are still unclear. We first showed that forced Bag‐1 expression promotes cell survival and prevents drug‐induced apoptosis in MCF‐7 breast cancer cells. Increased mRNA expressions of c‐myc protooncogene and ornithine decarboxylase (ODC), biosynthetic enzyme of polyamines, were detected in Bag‐1L+ cells, and western blots against the protein product of c‐Myc and ODC confirmed these findings. Once ODC, a c‐Myc target, gets activated, polyamine biosynthesis increases. We observed enhanced polyamine content in the Bag‐1L+ cells. On the contrary, when polyamine catabolic mechanisms were investigated, Bag‐1 silencing suppressed biosynthesis of polyamines because of the downregulation of ODC and upregulation of PAO. Exposure of cells to apoptotic inducers enhances the cell death mechanism by producing toxic products such as H2O2 and aldehydes. Bag‐1L+ cells prevented drug‐induced PAO activation leading to a decrease in H2O2 production following cisplatin or paclitaxel treatment. In this line, our results suggested that Bag‐1 indirectly affects cell survival through c‐Myc activated signalling that causes elevation of ODC levels, leading to an increase of the polyamine content. Copyright © 2015 John Wiley & Sons, Ltd.